2021
DOI: 10.1177/01708406211030659
|View full text |Cite
|
Sign up to set email alerts
|

How Structural Empowerment Boosts Organizational Resilience: A case study in the Dutch home care industry

Abstract: Previous work has demonstrated that structural forms of empowerment tend to enhance individual and team resilience. However, there is hardly any knowledge about how structural empowerment affects organizational resilience. Moreover, a widespread (though largely untested) assumption is that, in adverse times, power and authority need to be centralized at the top rather than decentralized, to enhance organizational resilience. This paper explores the effects of empowerment on organizational ¬¬resilience in an in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 93 publications
(147 reference statements)
1
34
0
1
Order By: Relevance
“…Different authors argued that organic structures are an important condition for greater connectedness among employees, which allows fast and situation-specific responses to adversity (e.g., Burke, 2005; van der Vegt, Essens, Wahlström, & George, 2015). In a recent case study of the Dutch home care industry, van den Berg, Alblas, Le Blanc, and Romme (2021) found that structural empowerment was positively linked to organizational resilience. Moreover, Chewning, Lai, and Doerfel (2013) observed that adaptive information and communication technologies predicted resilient organizational behaviors (i.e., information sharing, (re)connection, and resource acquisition).…”
Section: Organizational-level Resilience Literature Reviewmentioning
confidence: 99%
“…Different authors argued that organic structures are an important condition for greater connectedness among employees, which allows fast and situation-specific responses to adversity (e.g., Burke, 2005; van der Vegt, Essens, Wahlström, & George, 2015). In a recent case study of the Dutch home care industry, van den Berg, Alblas, Le Blanc, and Romme (2021) found that structural empowerment was positively linked to organizational resilience. Moreover, Chewning, Lai, and Doerfel (2013) observed that adaptive information and communication technologies predicted resilient organizational behaviors (i.e., information sharing, (re)connection, and resource acquisition).…”
Section: Organizational-level Resilience Literature Reviewmentioning
confidence: 99%
“…The latter directly influences any(emerging) underlying empowerment practice, but also in an indirect way by means of its impact on psychological safety. This study features benefit of engagement in nontrivial choices that move past the work unit (van Den Berg et al, 2021). Harter et al (2002) stated that when leaders and organizations fulfill the basic needs of employees, they feel more engaged at work.…”
Section: Process Innovation (Pi)mentioning
confidence: 99%
“…The latter directly influences any(emerging) underlying empowerment practice, but also in an indirect way by means of its impact on psychological safety. This study features benefit of engagement in nontrivial choices that move past the work unit (van Den Berg et al, 2021).…”
Section: Literature Review and Theoretical Underpinningsmentioning
confidence: 99%
“…Encouraging interactions with experienced nurses, appreciation, input and joint conversations about care delivery are all examples of structural empowerment. Nurses' stressful work environments have an impact on patient care, workplace culture adaptation and intention to leave (van den Berg et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%